179k views
2 votes
-x -6

Given: y= --------
2
Write the equation in general form Ax + By + C =0

User Dumi Jay
by
6.1k points

1 Answer

3 votes

Answer:

-6 = 1x + 2y

Explanation:

I sympathize: sometimes it's hard to format equations properly through this medium. Now I see that you meant:

-x - 6

-------- = y

2

To rewrite this in standard form, which is Ax + By = C, mult. both sides by 2. You'll get -x -6 = 2y. Now add x to both sides so as to have both x and y on one side and a constant on the other: -6 = 1x + 2y

User Pujan Shah
by
6.4k points